2018
DOI: 10.1002/gj.3344
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleogene strike‐slip transition of the Tan–Lu Fault Zone across the southeast Bohai Bay Basin: Constraints from fault characteristics in its adjacent basins

Abstract: The Tan–Lu Fault Zone (TLFZ) is the largest continental‐scale strike‐slip fault zone in East China. It experienced a complex Meso‐Cenozoic deformation and controlled the development and evolution of the Bohai Bay Basin (BBB). Though its Mesozoic sinistral and Cenozoic dextral motions have been well documented, its strike‐slip transition history and mechanism from sinistral to dextral motions in the Early Paleogene remain poorly understood. To investigate these issues, we made a thorough analysis on the fault g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Uchimura et al (1996) attributed the driving force of the tectonic rotation to post-Cretaceous large-scale sinistral faulting, up to ~ 800 km, along the Tan-Lu Fault. Although it was an active sinistral fault during the period when the first clockwise rotation is estimated to have occurred (Wang et al 2019), geological evidence does not suggest such large post-Cretaceous sinistral offsets. Lin et al (2003) proposed a clockwise tectonic rotation (i.e., first-phase rotation), primarily based on paleomagnetic data from the Benxi area and the Korean Peninsula (Fig.…”
Section: First Rotationmentioning
confidence: 99%
“…Uchimura et al (1996) attributed the driving force of the tectonic rotation to post-Cretaceous large-scale sinistral faulting, up to ~ 800 km, along the Tan-Lu Fault. Although it was an active sinistral fault during the period when the first clockwise rotation is estimated to have occurred (Wang et al 2019), geological evidence does not suggest such large post-Cretaceous sinistral offsets. Lin et al (2003) proposed a clockwise tectonic rotation (i.e., first-phase rotation), primarily based on paleomagnetic data from the Benxi area and the Korean Peninsula (Fig.…”
Section: First Rotationmentioning
confidence: 99%
“…Tectonically, the Luxi Terrane experienced a complex tectonic evolution and deformation history since the Mesozoic (Grimmer et al, 2002; G. Wang, Li, et al, 2019). During the Indosinian to Yanshan orogen, the Luxi Terrane underwent the intense compression, the direction shifted from SN to NW‐SE, which generated massive folds and thrust nappe (G. Wang, Liu, et al, 2013; F. Yang, Santosh, Glorie, Jepson, & Kim, 2020).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Tectonically, the Luxi Terrane experienced a complex tectonic evolution and deformation history since the Mesozoic (Grimmer et al, 2002;G. Wang, Li, et al, 2019).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The TLFZ, a typical strike‐slip fault zone, runs through the eastern border of the BBB (Figure 2), which is generally accepted to have originated from the collision of the South China Block and North China Block in the Late Triassic (Chen et al, 2022; Zhu et al, 2009), and the left‐lateral strike‐slip motion of the TLFZ during the Mesozoic was controlled by the subduction of the Izanagi‐Pacific Plate (Chen et al, 2022; Wang et al, 2019; Zhu et al, 2005). From the Cenozoic, the fault slip changed from normal faulting to right‐lateral motion during the Late Palaeogene (Chen et al, 2022; Wang et al, 2019), but the timing and mechanism of the right‐lateral strike‐slip are still controversial. Present‐day earthquakes have suggested that the fault zone is still active (Fu et al, 2004; Hsiao et al, 2004; Huang et al, 2018; Teng et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%